The role of sonic hedgehog homologue signal pathway in hypospadias aetiology - Sarac, Mehmet; Canpolat, Senay; Etem, Ebru Onalan; Tektemur, Ahmet; Tartar, Tugay; Bakal, Unal; Kazez, Ahmet (Elsevier Sci Ltd, 2021)
Summary Introduction Hypospadias is one of the most common congenital anomalies of the male genitalia. Sonic hedgehog homologue (SHH ) signalling pathway is believed to be involved in the development of the male genital system. Objective In this clinical prospective study, the role of the SHH pathway in hypospadias aetiology was investigated. Study design In this study, 200 healthy children (boys without hypospadias, control group), 118 patients (boys with distal hypospadias) and 82 patients (boys with proximal hypospadias) of age 0-16 years were included. The expression of the genes suppressor of fused protein (SUFU), SHH, protein patched homologue (PTCH; PTCH1 and PTCH2), glioma-associated oncogene homologue (GLI; GLI1, GLI2, GLI3 and GLI4), smoothened, frizzled-class receptor (SMO) and serine/threonine-protein kinase 36 (STK36) that are involved in SHH pathway were investigated. Furthermore, polymorphism analyses of GLI2, SHH and PTCH1 genes were performed. The history of hypospadias in the first and second-degree relatives of the patients in boys with distal hypospadias and boys with proximal hypospadias was inquired. Results Ten patients in the boys with distal hypospadias and twenty patients in the boys with proximal hypospadias had a history of hypospadias in first or seconddegree relatives (p < 0.05). There was a significant decrease in mRNA expressions of SHH and PTCH1 genes in boys with proximal hypospadias compared to boys without hypospadias (p < 0.05). Besides, a significant decrease in mRNA fold-change of GLI2 gene was detected in boys with both distal hypospadias and proximal hypospadias compared to boys without hypospadias (p 0.05). In contrast, there was no significant difference in the mRNA fold changes of PTCH2, SUFU, GLI1, GLI3, GLI4, SMO and STK36 genes among the groups. Moreover, there were no significant differences in the frequencies of variant genotypes and alleles rs735557, rs12711538 and rs4848632 (GLI2 gene), rs104894049 (SHH gene) and rs41313327 (PTCH1 gene) (p 0.05). Discussion SHH expression is required for the growth and differentiation of the genital bulge. Developmental defects in the external genital organs were demonstrated in mice with SHH deletion. It has been demonstrated that SHH mainly plays a role in the formation of sinusoid morphology of the penis. In the present study, although SHH and PTCH gene expressions were found to be decreased only in the penile tissues of proximal hypospadias, GLI2 gene expression was decreased in penile tissues of boys with both distal hypospadias and boys with proximal hypospadias. Conclusion Genes involved in the SHH pathway might play a role in the aetiology of hypospadias. Furthermore, there is a correlation between molecular defects in this pathway and severity of hypospadias.
Keywords: Hypospadias; Molecular; Ge-netics; Sonic hedgehog; Patched homolog 1; Glioma-associated oncogene homolog 2